2015
DOI: 10.1002/anie.201505704
|View full text |Cite
|
Sign up to set email alerts
|

Rechargeable Hydrogen Storage System Based on the Dehydrogenative Coupling of Ethylenediamine with Ethanol

Abstract: A novel and simple hydrogen storage system was developed, based on the dehydrogenative coupling of inexpensive ethylenediamine with ethanol to form diacetylethylenediamine. The system is rechargeable and utilizes the same ruthenium pincer catalyst for both hydrogen loading and unloading procedures. It is efficient and uses a low catalyst loading. Repetitive reversal reactions without addition of new catalyst result in excellent conversions in both the dehydrogenation and hydrogenation procedures in three cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(53 citation statements)
references
References 65 publications
1
52
0
Order By: Relevance
“…[12][13][14] Nowadays, hydrogen storager epresents at echnological challenge. [23][24][25][26][27] In this work, we have evaluatedt he potential of the amine/nitrile paira saliquid organic hydrogen carrier,a s suggested by Grelliera nd Sabo-Etienne in af rontier-type article (Scheme 1). [17][18][19][20] In this sense, the technological problems are minimized as the actuali nfrastructure is basedi nl iquidsf or storage and transport.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Nowadays, hydrogen storager epresents at echnological challenge. [23][24][25][26][27] In this work, we have evaluatedt he potential of the amine/nitrile paira saliquid organic hydrogen carrier,a s suggested by Grelliera nd Sabo-Etienne in af rontier-type article (Scheme 1). [17][18][19][20] In this sense, the technological problems are minimized as the actuali nfrastructure is basedi nl iquidsf or storage and transport.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Pez et al have reported ah ydrogen storage system involving the hydrogenation and dehydrogenation of N-ethylcarbazole (Scheme 1a). However, different metal catalysts have to be employed for the hydrogenation and dehydrogenation processes.F rom the standpoint of practical applications,t he use of as ingle catalyst which promotes both hydrogenation and dehydrogenation is desirable.P revious examples in which hydrogenation and dehydrogenation of nitrogen-containing organic hydrides were achieved by employing as ingle catalyst are shown in Schemes 1b-e. [7][8][9][10] However,t he following problems still remain with these systems:1 )a high pressure of hydrogen (> 49 atm) is required in the hydrogenation process and 2) a relatively large amount of solvent is always used. However, different metal catalysts have to be employed for the hydrogenation and dehydrogenation processes.F rom the standpoint of practical applications,t he use of as ingle catalyst which promotes both hydrogenation and dehydrogenation is desirable.P revious examples in which hydrogenation and dehydrogenation of nitrogen-containing organic hydrides were achieved by employing as ingle catalyst are shown in Schemes 1b-e. [7][8][9][10] However,t he following problems still remain with these systems:1 )a high pressure of hydrogen (> 49 atm) is required in the hydrogenation process and 2) a relatively large amount of solvent is always used.…”
mentioning
confidence: 99%
“…22 Lately, our group reported the development of hydrogen storage systems based on amide bond formation. 23 Ruthenium- and iridium-catalyzed dehydrogenative coupling of alcohols with substituted hydrazines are known as well, 24 but the direct use of N 2 H 4 in catalysis is very challenging. Very recently, Ru-catalyzed reaction of primary alcohols with hydrazine resulted in alcohol deoxygenation.…”
mentioning
confidence: 99%